A Phosphoinositide-Binding Protein Acts in the Trafficking Pathway of Hemoglobin in the Malaria Parasite Plasmodium falciparum - Mukherjee, Angana; Crochetière, Marie-Ève; Sergerie, Audrey; Amiar, Souad; Thompson, L Alexa; Ebrahimzadeh, Zeinab; Gagnon, Dominic; Lauruol, Florian; Bourgeois, Alexandra; Galaup, Thomas; Roucheray, Stéphanie; Hallée, Stéphanie; et al. (mBio, 2022)
Phosphoinositide lipids play key roles in a variety of processes in eukaryotic cells, but our understanding of their functions in the malaria parasite Plasmodium falciparum is still very much limited. To gain a deeper comprehension of the roles of phosphoinositides in this important pathogen, we attempted gene inactivation for 24 putative effectors of phosphoinositide metabolism. Our results reveal that 79% of the candidates are refractory to genetic deletion and are therefore potentially essential for parasite growth. Inactivation of the gene coding for a Plasmodium-specific putative phosphoinositide-binding protein, which we named PfPX1, results in a severe growth defect. We show that PfPX1 likely binds phosphatidylinositol-3-phosphate and that it localizes to the membrane of the digestive vacuole of the parasite and to vesicles filled with host cell cytosol and labeled with endocytic markers. Critically, we provide evidence that it is important in the trafficking pathway of hemoglobin from the host erythrocyte to the digestive vacuole. Finally, inactivation of PfPX1 renders parasites resistant to artemisinin, the frontline antimalarial drug. Globally, the minimal redundancy in the putative phosphoinositide proteins uncovered in our work supports that targeting this pathway has potential for antimalarial drug development. Moreover, our identification of a phosphoinositide-binding protein critical for the trafficking of hemoglobin provides key insight into this essential process. IMPORTANCE Malaria represents an enormous burden for a significant proportion of humanity, and the lack of vaccines and problems with drug resistance to all antimalarials demonstrate the need to develop new therapeutics. Inhibitors of phosphoinositide metabolism are currently being developed as antimalarials but our understanding of this biological pathway is incomplete. The malaria parasite lives inside human red blood cells where it imports hemoglobin to cover some of its nutritional needs. In this work, we have identified a phosphoinositide-binding protein that is important for the transport of hemoglobin in the parasite. Inactivation of this protein decreases the ability of the parasite to proliferate. Our results have therefore identified a potential new target for antimalarial development.
Keywords: Animals; transportní proteiny; Plasmodium falciparum; protozoální proteiny; paraziti; tropická malárie; Malaria, Falciparum; erytrocyty; Protozoan Proteins; Malaria; lidé; Parasites; Carrier Proteins; antimalarika; fosfatidylinositoly; Erythrocytes; Hemoglobins; hemoglobiny; Phosphatidylinositols; zvířata; malárie; Antimalarials; Humans